What is Online Research? Using the Internet for Social Science Research - Hooley, Tristram (The 'What is?' Research Methods Series, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The massive expansion of the internet into every aspect of our lives creates a challenge for social researchers: can they simply transfer their traditional methods and techniques online or do they need to reinvent research methods for the new environment? As online research becomes increasingly prevalent it becomes more important for researchers to have an answer to these questions and an approach to conducting research online. This book is a straightforward, accessible introduction to social research online. It covers the key issues and concerns for social scientists: online surveys, focus groups, interviews, ethnographies and experiments, as well as discussing the implications of social media, and of online research ethics. It provides a detailed, up-to-date glossary and bibliography for those new to the area. Short, clear case studies throughout allow students to see examples of the research in practice. Wide-ranging and interdisciplinary, What is Online Research? shows social scientists of all levels - from undergraduates to established researchers - how to engage in the online environment in appropriate ways, and points the way forward for future research.